2022
DOI: 10.3934/cpaa.2022137
|View full text |Cite
|
Sign up to set email alerts
|

Stable standing waves of nonlinear fractional Schrödinger equations

Abstract: We study the existence and orbital stability of standing waves of nonlinear fractional Schrödinger equations with a general nonlinear termWe investigate the minimizing problem with L 2 -constraint:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…The authors of this article [29] have already showed that there exists α 0,∞ ∈ [0, ∞] uniquely determined by N, s and f such that…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The authors of this article [29] have already showed that there exists α 0,∞ ∈ [0, ∞] uniquely determined by N, s and f such that…”
Section: Introduction and Main Resultsmentioning
confidence: 99%